A DYNAMIC AND MULTIVARIATE ANALYSIS OF TREASURY BILL BEHAVIOR IN A BANK ASSET PORTFOLIO - Takele, Yitbarek (European Scientific Journal, ESJ, 2013)
The portfolio behavior of banks in a developing financial market environment is somewhat different from that of developed markets. To explore such a situation, in this study, a dynamic and multivariate analysis of the behavior of treasury bills in the bank's asset portfolio is employed by using data from the Ethiopian banking sector. A very comprehensive econometric model that includes initial stock variable, asset portfolio variables, liability portfolio variables, and yield differentials has been developed. The study is time series and covers the period from the first quarter of 2000 to second quarter of 2010 of the Ethiopian banking sector. Except for the yield differentials other variables are found to be significant. Besides, all the explanatory variables maintain the a priori expected sign except one of the yield differentials: relative yield differential between long-term and short-term securities. This is attributed to the less attractive and more stable nature of the yield on long-term securities in the Ethiopian financial market.